2014
DOI: 10.4103/2229-3485.124557
|View full text |Cite
|
Sign up to set email alerts
|

Revised National Tuberculosis Control Program regimens with and without directly observed treatment, short-course: A comparative study of therapeutic cure rate and adverse reactions

Abstract: Objective:To compare the therapeutic cure rate and adverse reactions in the regimens of the Revised National Tuberculosis Control Program (RNTCP) with directly observed treatment, short-course (DOTS) and without DOTS.Materials and Methods:Fifty patients in the DOTS regimen and 50 patients in the non-DOTS regimen were enrolled in the study. All the participants were asked to come regularly for 3 consecutive days for sputum collection, and the sputum samples were examined for acid-fast bacilli. If tuberculosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The TB is an important health problem in Iran and the issue has become even more and therefore, as a result of increasing drug-resistant strains, drug resistance complicates efforts to control TB. Moreover, the problem of extensively drug-resistant strains has recently been introduced ( 14 , 15 ). Despite effective drugs and diagnostic methods, TB is one of the main killers of humanity throughout history and is still growing ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TB is an important health problem in Iran and the issue has become even more and therefore, as a result of increasing drug-resistant strains, drug resistance complicates efforts to control TB. Moreover, the problem of extensively drug-resistant strains has recently been introduced ( 14 , 15 ). Despite effective drugs and diagnostic methods, TB is one of the main killers of humanity throughout history and is still growing ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of ADRs with first-line anti-tuberculosis drugs is estimated to vary from 2.3% to 17% in various Indian studies. 10,12,15,20,[22][23][24]26,27 A study conducted by Mehrotra et al observed that the prevalence of ADRs in the initial intensive phase was 17.39%. 34 Another study conducted at a tertiary institute in Calcutta observed that the overall toxicity was found in 35% cases in the daily regimen group, whereas it was found to be 27.9% in the intermittent regimen group.…”
mentioning
confidence: 99%
“…Directly Observed Treatment Short course (DOTS) is one of the most cost-effective approaches to TB treatment [3,4]. The cure rate of TB was 82% among patients participating in the DOTS strategy worldwide, significantly higher than among those who did not take part in tDOTS (68%), in 2002 [5].…”
Section: Introductionmentioning
confidence: 99%